Geocriticism and the exploration of Mexico City-Tenochtitlán in Carlos Fuentes’ Where the Air is Clear - Pasuree Luesakul (Penerbit Universiti Kebangsaan Malaysia, 2022)
Where the Air is Clear, or La región más transparente (1958) in its original version, is an urban fiction of Mexico City structured from a postcolonial perspective by Carlos Fuentes, one of Latin American Boom authors. This literary biography of 1950s Mexico’s capital is portrayed with a double complexity. On one hand, the modern but chaotic space is presented through a narrative fragmentation composed of a “chorus” of inhabitants from different social classes and neighbourhoods. On the other, the author depicts a total image of the megacity by highlighting its historical particularity: Mexico City was constructed by Spaniards precisely above the ruins of Tenochtitlán, the capital of the Aztecs. This article proposes a study of the Boom’s classic text with a novel approach from a geographical focus. The methodology utilized is Bertrand Westphal’s Geocriticism (2007) that aims to explore a space’s fictionalization from a multidisciplinary approach, in this case, literature, history and geography, and with the use of cartographic representations. This analysis is, thus, “mapped” from the perspective of Ixca Cienfuegos, an indigenous character with supernatural powers who explores the space of Mexico City-Tenochtitlán through two key years: 1951—the Dystopia of Mexico City where modernity cohabitates with antiquity, and prosperity with poverty— and 1519 —the Utopian past of Tenochtitlán before the landscape’s transformation under Spanish colonization.